A new method for assessment of burst pressure capacity of corroded X80 steel pipelines containing a dent. (October 2022) - Zhao, Jian; Lv, Yunrong; Cheng, Y. Frank
Abstract: This work developed a new finite element (FE)-based method to perform pressure capacity assessment on a corroded X80 steel pipe containing a dent, where their mutual interaction and the effect on further corrosion growth were defined. Parametric effects including corrosion depth, dent depth, corrosion length and service time were determined. The presence of a dent at corrosion defect remarkably changes the local stress distribution, elevating stress to plastic range. The mutual interaction between the dent and the corrosion defect depends on both the initial corrosion depth and the initial dent depth. The interaction remarkably changes the local stress level at the dent and must be included in pipeline burst failure assessment. Highlights: Developed a new assessment method for pressure capacity of corroded X80 steel pipelines containing a dent. Determined the mutual interaction of corrosion defect and dent on failure pressure. Determined the corrosion defect growth rate in the presence of dent on pipelines.